Branderpreneurship Framing Analysis of Koperasi Desa Merah Putih - Muhammad Dicky Arfani; Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2026)
Koperasi Desa Merah Putih (Kopdes MP) is a strategic government initiative aimed at revitalizing Indonesian cooperatives through a modern, transparent, and digitally-driven brand image. This study is prompted by the gap between the policy vision of rural economic empowerment and its execution in the field. It aims to analyze how Kopdes MP designs, builds, and executes brand values using the Branderpreneurship framework and the BrandCoVD model, spanning the processes of identifying, creating, delivering, communicating, maintaining, evaluating, and updating values. Utilizing a Branderpreneurship Framing Analysis (BFA) method with a descriptive qualitative approach, data were gathered via policy document reviews, pilot unit observations, and branding practice analysis. Findings indicate that while Kopdes MP holds vast potential as a modern cooperative ecosystem, it faces critical challenges: a centralized, top-down hiring process that marginalizes local communities and core cooperative values, the deployment of the Kopdes Mobile MP application without sufficient training resulting in self-taught adaptation, and inconsistent brand value distribution that renders messages rhetorical. The success of Kopdes MP depends on managerial capacity to fulfill brand promises through transparent governance, human resource development, and ongoing evaluation. This study underscores that differentiating functional, emotional, cultural, and social values is key to building public trust and establishing an adaptive, sustainable cooperative model.